PAST, PRESENT AND FUTURE: THE IMAGINARY “BECOMING” OF PEOPLE WHO USE TO EXERCISE IN OUTDOOR GYMS FOR SENIOR CITIZENS IN LAGES/SC (Fiep Bulletin - online, 2013)
This paper has as objective to discuss the imaginary matter of people who use to work out in outdoor Gyms for Senior Citizens ATIs, in order to approach the “becoming” perspective for a behavior changing through physical activities and relations which are established in that social field. Interviews with those subjects have submitted to the construction of the image of their bodies in which both, subject and body, are modified and, this way, other perspectives are opened. Knowledge reconstruction in relation to body which is moving can be changed while the “becoming” of that imaginary is configured in a new initiative of people from ATIs.
Keywords: Gym for Senior Citizens; imaginary; body.